2011
DOI: 10.1128/mbio.00142-11
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide (LPS) Inner-Core Phosphates Are Required for Complete LPS Synthesis and Transport to the Outer Membrane in Pseudomonas aeruginosa PAO1

Abstract: Gram-negative outer membrane (OM) integrity is maintained in part by Mg2+ cross-links between phosphates on lipid A and on core sugars of adjacent lipopolysaccharide (LPS) molecules. In contrast to other Gram-negative bacteria, waaP, encoding an inner-core kinase, could not be inactivated in Pseudomonas aeruginosa. To examine this further, expression of the kinases WaaP or WapP/WapQ/PA5006 was placed under the control of the arabinose-regulated pBAD promoter. Growth of these strains was arabinose dependent, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 54 publications
3
61
0
Order By: Relevance
“…Since LptD mediates the distal transport of mature LPS, its absence should cause some accumulation of varied forms of LPS in the membrane(s), since the machinery to synthesize intact LPS is present in lptD::Km r mutant cells. However, electron microscopy did not reveal any gross membrane defects in the lptD::Km r mutant like those described previously for P. aeruginosa upon interference with LPS transport (13,14,48). Since A. baumannii ATCC 19606 tolerates the absence of LptD and can apparently compensate somewhat for the lack of normal LPS transport, this defect itself may not be expected to manifest such pronounced morphological changes.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Since LptD mediates the distal transport of mature LPS, its absence should cause some accumulation of varied forms of LPS in the membrane(s), since the machinery to synthesize intact LPS is present in lptD::Km r mutant cells. However, electron microscopy did not reveal any gross membrane defects in the lptD::Km r mutant like those described previously for P. aeruginosa upon interference with LPS transport (13,14,48). Since A. baumannii ATCC 19606 tolerates the absence of LptD and can apparently compensate somewhat for the lack of normal LPS transport, this defect itself may not be expected to manifest such pronounced morphological changes.…”
Section: Discussionmentioning
confidence: 77%
“…Interference with LptD-mediated LPS translocation in P. aeruginosa caused aberrant membrane-like material to accumulate within the periplasm (13). Similarly, depletion of WaaP, an essential kinase required for LPS core synthesis, caused the accumulation of truncated LPS in the IM, attributed to an inability to transport this aberrant LPS to the OM (48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low similarity to pyruvate kinase, a phosphotransferase, suggests that this enzyme is involved in the transfer of phosphates to or from the O-antigen-lipid carrier molecule as part of the ligation process. Alternatively, this enzyme may phosphorylate lipid A-core inside the cell, as occurs in the lipid A of other bacteria, including Pseudomonas aeruginosa, where phosphorylation of lipid A-core is required for LPS transport to the outer membrane (50). The presence of phosphorus has already been demonstrated in the LPS of Anacystis nidulans KM (18), a strain since considered S. elongatus.…”
Section: Discussionmentioning
confidence: 99%
“…Our results also indicated that the rfaC (waaC) deletion strain 10031 was highly sensitive to polymyxin B (Table 3). This may be in part due to the loss of stabilizing LPS cross-links mediated through the core, leading to a defect in the permeability barrier (62).…”
Section: Discussionmentioning
confidence: 99%